The Impact of Business Continuity Management on the German Energy Sector During the Russia-Ukraine Conflict - Kalirad, Mojtaba (Global journal of Business and Integral Security, 2025)
The war between Russia and Ukraine in 2022 has tabled many shocks to the global value chains of many items and tested how global networks for commerce convey energy. This study aimed to assess the organization’s Business continuity management (BCM) and its ability to provide resilience and continuity improvement solutions as a major German energy company, Uniper. Thus, the case of Uniper is analyzed as a case study of how BCM principles are implemented in practice at the company level in the context of this research, which examines business continuity planning and readiness in the context of geopolitics. The research investigated how well the German energy firm has integrated BCM into its operations, with an emphasis on business continuity planning and readiness methods. Furthermore, this study aimed to raise knowledge and understanding of BCM’s importance in organizational sustainability, hence improving the company’s capacity to handle difficult situations. The research data was collected from workers at the German energy firm using 200 questionnaires. The survey’s target audience comprised managers, human resource officers, operations managers, and information and communications technology (ICT) administrators from the organization. After gathering the data, statistical software for the social sciences (SPSS) version 20 was used for data analysis, including correlation and regression analysis methods. The review shed light on the link between BCM implementation and the company’s capacity to effectively manage emergencies, as well as highlighted opportunities for development. The study’s findings are intended to give useful insights into the applicability and impact of BCM on organizational resilience in energy companies, particularly in the context of crisis management following the Russian-Ukrainian war. This study aims to add to the body of knowledge on business continuity and crisis management techniques by identifying areas of strength and weakness with particular relevance for a German energy company. The findings of this study provide practical advice for German energy companies on how to improve their resilience and preparation in the face of potential future crises and uncertainties. This research provides significant insights into the specialized frameworks employed by German energy supply companies to manage crises, particularly during the Russia-Ukraine conflict. The study confirms the existence and general effectiveness of these frameworks in enhancing operational continuity and financial stability. Keywords: Global energy market, German energy sector, business continuity management, operational continuity, financial stability, resilience strategies, crisis management strategies, energy supply chains, energy company.